ANALISIS DAMPAK PENGGUNAAN S-PAY LATER TERHADAP PERILAKU KEUANGAN MAHASISWA DI ERA EKONOMI DIGITAL - Sitorus, Onny Fitriana; Haryati, Eka (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
Digital developments have a major impact on various sectors, one of which is the economy. The digital economy era provides innovation in payment methods on various business platforms, namely using the S-Pay Later method, one of the most popular choices among the younger generation. The research method used in this study is descriptive quantitative by distributing questionnaires to collect data from students living in the UHAMKA dormitory. Based on the results of the analysis, it shows that the use of S-Pay Later can affect students' financial behavior, both in terms of spending, savings, and money management. Students who use S-Pay Later said that they find it easier to make payments, but they also tend to make more impulsive purchases and have difficulty managing their finances. The purpose of this study is to educated on the importance of financial management for students in increasing awareness and the impact of using digital payment services. This study is intended to provide insight to educational institutions to design programs that support students in managing their finances wisely.